The Perception of Customers Towards Sustainable Practices in Indian Banks - E. S., Sina; Vennila, D. (Ushus Journal of Business Management, 2023)
Sustainable Development (SD) is currently becoming more well-known. As a result, many kinds of organizations are working together to guarantee that sustainable development is noticed in pursuing their objectives, such as profit-making, providing social services, philanthropy, etc. Sustainable development (SD) is preserving the integrity of social and natural systems while pursuing economic growth. Non-Financial Reporting is a framework for organizations to report on their operations in this area, particularly about the triple bottom line or the accounting of the environment, society, and economy. Given their critical role in funding global economic and developmental activities, financial institutions, particularly banks, must contribute significantly to sustainable development. In this context, it is challenging to overstate how important it is for banks to behave responsibly as corporate citizens in society, particularly in a growing nation like ours. Their actions should demonstrate how they care about the environment and human rights. This paper emphasizes the significance of "Going green" and promoting sustainable practices in the Indian banking sector. The perception of customers toward Sustainable practices in Indian banks has not been the subject of much research. The study aims to comprehend how consumers feel about green banking services and their effectiveness and benefits. Friedman Ranking test and Chi-Square have been used as tools for the analysis.